How Consistent are Course Grades? An Examination of Differential Grading - Rauschenberg, Samuel (Education Policy Analysis Archives, 2014)
Differential grading occurs when students in courses with the same content and curriculum receive inconsistent grades across teachers, schools, or districts. It may be due to many factors, including differences in teacher grading standards, district grading policies, student behavior, teacher stereotypes, teacher quality, and curriculum adherence. If it occurs systematically, certain types of students may receive higher or lower grades relative to other students, despite having similar content mastery or ability. Using three years of statewide data on Algebra I and English I courses in North Carolina public high schools, I find that student characteristics are stronger predictors of differential grading than teacher, school, or district characteristics. Female, Limited English Proficient, and 12th grade students earn statistically significant higher grades than other students, holding test scores and student, teacher, school, and district characteristics constant. Low-income students, conversely, earn lower grades than other students, all else constant. With the exception of Algebra I low-income students, these differences are large enough to move a student one grade category on a plus/minus 7-point A-F grading scale. Black students earn higher Algebra I grades but lower English I grades than white or Asian students with the same test score, but these effect sizes are smaller than other student characteristics. Interactions between student and teacher race and gender yielded small estimates that were not consistent between subjects.